Faktor – Faktor Yang Mempengaruhi Perencanaan Keuangan Keluarga Secara Syariah ( Studi Kasus Di Desa Puspasari Kecamatan Citeurep Kabupaten Bogor ) - Farhan Dwi Aditya; Ahmad Mulyadi Kosim; Hilman Hakiem (CV. ITTC INDONESIA, 2024)
Islamic economics aims to achieve falah, namely happiness and welfare through fair management of resources in accordance with maqashid sharia, which includes the welfare of religion, soul, mind, descendants, and property. However, in practice, many Muslim families do not fully understand or apply the principles of financial management taught in the Qur'an and Hadith. This study aims to analyze the influence of financial literacy, education level, and income level on family financial planning according to sharia in Puspasari Village, Citeureup District, Bogor Regency. The method used is a quantitative approach by collecting data through a survey of Muslim families in the village. The results of the study indicate that the level of education, income, and family financial literacy have a significant effect on sharia financial planning. Although most families have done financial planning, there are still shortcomings in terms of detailed planning in accordance with sharia principles, especially related to the management of emergency funds and unexpected expenses. This study provides recommendations for the community to better understand and implement sharia-compliant family financial planning to improve family welfare in the long term.